Unlocking Learner Potential Through Well-being: A Conceptual Framework for Integrating Positive Psychology to Foster Deep English Language Learning - Nur, Sahril; Sakkir, Geminastiti; Nurfadhilah, Auliyanti Sahril (Yayasan Cendekiawan Indonesia Timur, 2025)
Second language (L2) learning is often undermined by significant psychological barriers like anxiety and fragile motivation, trapping students in surface-level memorization. This conceptual paper proposes a fundamental paradigm shift from a deficit-remediation model to one centered on fostering learner well-being. Drawing on a systematic literature review, we introduce 'Positive Language Pedagogy,' a framework integrating the five pillars of positive psychology's PERMA model (Positive Emotions, Engagement, Relationships, Meaning, Accomplishment). We argue that this systematic integration proactively dismantles affective filters, cultivates intrinsic motivation, and builds psychological resources essential for deep learning. The result is a pathway toward not only linguistic competence but also the development of resilient, autonomous, and confident language learners.